Efektivitas Pemanfaatan Aplikasi JKN Mobile pada Prosedur Pendaftaran Pasien Rawat Jalan Secara Online di RSUD Kota Baubau - Anna Maria Daud; Anggung Dinianti; Sulistyawaty Desy Resky; Muhajrin Muhajrin (Pusat Riset dan Inovasi Nasional, 2025)
The JKN Mobile application is an electronic-based service innovation introduced by BPJS Health to facilitate JKN participants in accessing healthcare services and managing their membership information. This study aims to explore the experiences and perspectives of outpatient patients regarding the effectiveness of the JKN Mobile online registration system at Baubau City Regional General Hospital. A qualitative phenomenological approach was employed, with informants selected through purposive sampling. Data were collected to capture the meanings of patients’ experiences in using the application. The findings show that most patients are satisfied with the practicality, speed, and flexibility of the online registration system. However, technical problems, particularly unstable internet connectivity, remain a major challenge. Furthermore, the online registration system has contributed to improved service efficiency and patient satisfaction. These findings indicate the importance of continuous evaluation and improvement of the JKN Mobile online registration system to enhance service quality and health information system development at Baubau City Regional General Hospital.